The humanitarian and development assistance program in Maguindanao province - Salipada, Tahir K.; Abdula, Sajid P.; Abdula, Datuali Paguital; Sura, Khairon A. (Edelweiss Applied Science and Technology, 2025)
The study aimed to determine the extent of the impact of the implementation of the Humanitarian and Development Assistance Program (HDAP) on social services, economic services, and peace and governance. It also evaluated the challenges encountered by the beneficiaries in the implementation of the program. The HDAP is a program of the Autonomous Region in Muslim Mindanao (ARMM) for the Maguindanao del Sur province. The study utilized a descriptive-evaluative design that employed a quantitative approach. It was conducted in the municipalities of Mamasapano and Datu Saudi Ampatuan, Maguindanao. The researcher employed the purposive sampling technique, where 50 respondents were selected from each municipality, for a total of one hundred (100) respondents. The gathered data was tallied, categorized, and analyzed using frequency, percentage, and mean. Results revealed that the extent of the impact of the implementation of HDAP was extensive, which implied that the program helped the residents of the local governments. The beneficiaries encountered delays in the delivery of services of the project, as well as the presence of peace and order conditions in the localities, which subsequently caused the delays in the services.